Meningkatkan Prestasi Belajar IPA Materi Kemagnetan melalui Metode Praktikum pada Siswa Kelas IX-A SMPN 21 Mataram - Rahmawati, Lindu (Lembaga Yasin AlSys, 2022)
This research is Classroom Action Research (PTK) which aims to improve science learning outcomes in Magnetism material which is carried out in class IX-A students of SMPN 21 Mataram using the practicum method. Before carrying out the action research, the researcher obtained the less satisfactory results of science learning achievement in class IX-A, this is indicated by the results obtained in the pre-cycle of 30 students who completed their studies as many as 14 students with the provision that the KKM score was 75, with an average student score of 66.3, the lowest score is 40 and the highest score is 85. Based on this, the researcher conducted action research with the aim of improving student learning outcomes on Magnetism using the practicum method. In carrying out action research the researcher did it in 2 stages, namely cycle I and cycle II. In cycle I the implementation of the action was carried out in two meetings, namely the first meeting with the sub material Magnetic Properties of Materials and the second meeting with the sub material How to Make Magnets. In the implementation of cycle I, the results were quite satisfactory, this was indicated by the results obtained from 30 students who had completed learning as many as 23 students with an average score of 75.5, the lowest score was 60 and the highest score was 95, but still below the completeness score. classical is 77%. In cycle II the implementation of the action was also carried out in two meetings, namely the third meeting with the Magnetic Induction sub-material and the fourth meeting with the Electromagnetic Induction sub-material. In the implementation of cycle II, very satisfying results were obtained, this was indicated by the results obtained from 30 students who had completed learning as many as 26 students with an average score of 75.8, the lowest score was 60 and the highest score was 100 and the classical completeness score was above 85. % that is 87%.